XIII wiek – stulecie przełomu w dziejach średniowiecznego szkolnictwa w Polsce - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2009)
The 13th century in the Piast Poland was marked by a feudal fragmentation of the Polish Kingdom and was heavily burdened with the deepening political disruption of the country resulting in economic and military weakening of the component principalities (dukedoms) of the country. This, in the next century, eventually led to some of the provinces falling into dependencies upon the Kingdom of Bohemia. However, what was destructive and divisive from the perspective of political history, offered a stimulating dimension for the history of culture and education, for the period in question was characterized by a multiplication of chanceries throughout the whole of the century, which, as a result, increased a demand for literate individuals. Colonization based on the Magdeburg Law (a set of German town laws) and the influx of foreigners into Polish lands: chief settlers (German: der Lokator), friars and monks from newly established Cistercian, Dominican and Franciscan orders as well as knights in service of ducal courts or representing military orders, in short, people deeply rooted in Western legal tradition, capable of making use of documents or written legal codification, boosted the phenomenon even more. The development of towns, trade relations between the principalities as well as international trade facilitated the emergence of capital that, alternatively, could also be used in founding schools of all kind. A considerable influence upon the following leaping increase in the number of schools and the quality of teaching standards in the country came from ecclesiastical synods and councils whose legislation regulated many relevant activities and issues related to management of schools, levels of education for applicants for teaching posts, or, more broadly, created appropriate intellectual climate favourable for further development of the schooling system. A number of the above factors, as well as other factors discussed in the body of the article, were decisive in making the thirteenth century a particularly significant period in the historical process of the development of Polish literary and educational culture.